MEMBANGUN BUDAYA SADAR HUKUM SISWA DALAM PEMAHAMAN HAK ASASI MANUSIA DI SEKOLAH - Yusdiyanto Yusdiyanto; Malicia Evendia; Martha Riananda; Ahmad Saleh; Dewi Nurhalimah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This Community Service activity aims to increase legal awareness of the community, especially the younger generation in understanding their own human rights and the importance of respecting the human rights of others within the framework of the rule of law. This is important so that students do not only promote the Human Rights inherent in themselves, but ignore the Human Rights which are also attached to others. The specific target of this activity is expected to be a solution and an effort to encourage a culture of law awareness so that the conditions for law-abiding and law-abiding among young people are increasingly created. So that the target audience in this activity is high school students. The location of the activity was carried out at MAN 1 Bandar Lampung. The method used in this activity is through lectures and discussions. It is hoped that after this activity is carried out, the participants will increase their understanding of Human Rights as regulated in laws and regulations so as to encourage the creation of a culture of legal awareness. The results of the activity show that: the legal awareness of the activity participants towards human rights has increased by up to 85%. This is indicated by several indicators including human rights; children's rights; the purpose of protecting human rights; regulation of human rights in Indonesia; and the importance of a litigious culture.